PIN versus Avalanche photodiode gain optimization in zero cross correlation optical code division multiple access system - Anuar, Mat Safar, Ir. Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Amir Razif Arief, Jamil Abdullah; Junita, Mohd Nordin; Mohamad Naufal, Mohamad Saad, Assoc. Prof. Dr. (Elsevier GmbH, 2013)
Link to publisher's homepage at http://www.elsevier.com/